The Relationship Between Activeness in Qur’anic Learning Activities and Emotional Intelligence of Students at SMAI Hidayatullah Tanjung Selor - Cahyo Utomo, Muhammad Irfandi; Sriyanto, Sriyanto; Noreng, Mustakim; Hardiansyah, Joddy; Prasetya, Benny (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2026)
The paradigm shift in Islamic education in the modern era demands a balance between the mastery of knowledge and the formation of personality rooted in spiritual values. Qur’anic learning is regarded as having a strategic role in developing students’ emotional intelligence through activities such as reading, memorizing, and understanding the meanings of the verses. This study aims to analyze the relationship between students’ activeness in Qur’anic learning activities and their emotional intelligence at SMA Integral Hidayatullah Tanjung Selor. Using a quantitative approach with a population method involving 63 students, data were collected through a five-point Likert-scale questionnaire and analyzed using Pearson correlation and simple linear regression. The results reveal a significant positive relationship between activeness in Qur’anic learning and emotional intelligence (r = 0.82; p < 0.01). This indicates that the more actively students participate in Qur’anic activities, the better their ability to manage emotions and demonstrate empathy toward others. These findings underscore the importance of participatory and reflective Qur’anic learning strategies as a means of strengthening emotional and spiritual intelligence in contemporary Islamic education.